Escharotic Therapy vs. Primary Facial Closure for Omphalocele: An Early Outcome Analysis - Bhairu L. Gurjar; Rahul Gupta (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Context: Omphalocele is a congenital midline periumbilical abdominal wall defect with the herniated visceral organs covered by a membrane. The morbidity and mortality of neonates with omphalocele in our geographical area are under-evaluated. Aims: The aim of the study was to compare the early outcomes of omphalocele using two different management modalities, that is, either escharotic therapy or primary facial closure from a high-volume institute in India. Settings and Design: This prospective observational study was undertaken over a one-year duration extending from January to December 2021 at our pediatric tertiary care teaching institute. Subjects and Methods: The study included all patients with omphalocele admitted to the neonatal intensive care unit. The decision for management of the neonates with either escharotic therapy or primary facial closure was performed as per the discretion of the unit head. Results: There were 16 neonates with omphalocele; 10 (62.5%) males and six (37.5%) females. The mean birth weight was 2575 ± 839 g (range = 1700–5000 g). Associated major malformations/syndromes were observed in five (31.25%) patients. Group A (escharotic therapy) had nine patients with major omphalocele and two patients with minor omphalocele. Group B (primary facial closure of the defect) constituted four minor omphaloceles and one omphalocele major with a ruptured sac. Out of 11 patients in group A, nine survived (favorable outcomes); the cause of death in two patients was associated with cyanotic heart disease and cloacal exstrophy. Out of the five patients in group B, two survived (favorable outcomes); the cause of death in two patients was postoperative sepsis due to ruptured sac and associated OEIS syndrome. One patient had multi-organ dysfunction syndrome as a consequence of abdominal compartment syndrome. Conclusions: The survival percentage of neonates with escharotic therapy (81.82%) was better than primary facial closure (40%). The creation of ventral hernia is a better modality of management in neonates with omphalocele, especially in a resource-limited center.